The Influence of Service Quality, Word of Mouth Price on Restaurant D'cost Kemang South Jakarta Purchasing Decision - Efendi, Nalam; Hardini, Resti; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This study aims to analyze the magnitude of the influence of Service Quality, Price, and Word Of Mouth (WOM) on the Purchasing Decision of Restaurant D'cost Kemang South Jakarta. This study used primary data by distributing questionnaires as many as 100 respondents. Data were analyzed using descriptive and inferential analysis. In the implementation of the study using primary data obtained through the distribution of questionnaires and processed with SPSS 17.0. The results showed that the variables of Service Quality, Price, and Word Of Mouth (WOM) had a positive and real influence on Purchasing Decisions of 0.906 which was classified as strong. While the coefficient of determination obtained R Square of 0.538 or 53.8% variation in the dependent variable, namely purchasing decisions can be explained by a combination of independent variables, namely, Service Quality, Price, and Word Of Mouth (WOM). While the remaining 4.62% can be explained or explained by other factors that the author did not study. Through regression values KP = 3.931 + 0.353 KP + 0.210 H + 0.285 WOM can be predicted regarding the ups and downs or size of employee performance.